2006
DOI: 10.1038/sj.ejcn.1602427
|View full text |Cite
|
Sign up to set email alerts
|

Effects of breakfast meal composition on second meal metabolic responses in adults with type 2 diabetes mellitus

Abstract: Objective: We tested the relative importance of a low-glycemic response versus a high glycemic response breakfast meal on postprandial serum glucose, insulin and free fatty acid (FFA) responses after consumption of a standardized mid-day meal in adult individuals with Type 2 diabetes mellitus (DM). Design: Following an overnight fast of 8-10 h, a randomized crossover intervention using control and test meals was conducted over a 3-week-period. A fasting baseline measurement and postprandial measurements at var… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
46
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 73 publications
(48 citation statements)
references
References 32 publications
2
46
0
Order By: Relevance
“…Breakfast consumption could result in an elevated postprandial glycaemic response and insulin sensitivity (25)(26)(27)(28)(29) , especially when the foods consumed are fibre-rich foods (i.e. whole grains, fruit and lowfat dairy) rather than refined cereals.…”
Section: Discussionmentioning
confidence: 99%
“…Breakfast consumption could result in an elevated postprandial glycaemic response and insulin sensitivity (25)(26)(27)(28)(29) , especially when the foods consumed are fibre-rich foods (i.e. whole grains, fruit and lowfat dairy) rather than refined cereals.…”
Section: Discussionmentioning
confidence: 99%
“…An earlier study (Clark et al, 2006) using a test meal found no evidence of any postprandial improvement in free fatty acids with psyllium treatment, but provided no data on lipoproteins. In our study, psyllium did not seem to reduce postprandial cholesterol and triglyceride levels.…”
Section: Discussionmentioning
confidence: 99%
“…The capacity of soluble fibers to decrease the postprandial glucose reaction to meals eaten some hours after fibre ingestion (second meal effect) was shown previously in non-diabetic individuals. It also reduced insulin recruitment in patient with diabetes mellitus [32,42].…”
Section: Diabetesmentioning
confidence: 99%